α6β4 Integrin, a Master Regulator of Expression of Integrins in Human Keratinocytes - Kligys, Kristina R. (American Society for Biochemistry and Molecular Biology, 2012)
Three major laminin and collagen-binding integrins in skin (α6β4, α3β1, and α2β1) are involved in keratinocyte adhesion to the dermis and dissemination of skin cells during wound healing and/or tumorigenesis. Knockdown of α6 integrin in keratinocytes not only results in motility defects but also leads to decreased surface expression of the α2, α3, and β4 integrin subunits. Whereas α2 integrin mRNA levels are decreased in α6 integrin knockdown cells, α3 and β4 integrin mRNAs levels are unaffected. Expression of either α6 or α3 integrin in α6 integrin knockdown cells restores α2 integrin mRNA levels. Moreover, re-expression of α6 integrin increases β4 integrin protein at the cell surface, which results in an increase in α3 integrin expression via activation of initiation factor 4E-binding protein 1. Our data indicate that the α6β4 integrin is a master regulator of transcription and translation of other integrin subunits and underscore its pivotal role in wound healing and cancer.